(untitled) (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
Some students have not been able to understand the learning styles that are in themselves, one of the learning styles is the kinaesthetic learning style. This Study aims to determine the mathematical communication skills of class X students with kinaesthetic learning styles. With the characteristics of kinaesthetic people will be easier to learn through physical activity and direct involvement in absorbing information. This research is a qualitative and descriptive study by taking subjects using purposive sampling. The subjects in this study were students of class X SMK Negeri 2 Semarang as many as 3 students with kinesthetic learning styles. The results of this study are the mathematical communication skills of student with kinaesthetic learning styles able to communicate mathematical ideas logically, provide clear explanations and be easily understood. Less able to bring up in expressing and organizing mathematical thought ideas in writing into mathematical models, and less able to bring up in terms of using the learning styles. The results of this study are the mathematical communication skills of students with kinesthetic learning styles able to communicate mathematical ideas logically, provide clear explanations and be easily understood. Less able to bring up in expressing and organizing mathematical thought ideas in writing into mathematical models and less able to bring up in terms of using the presentation of mathematical vocabulary and terminology in the form of writing and pictures.